دور التنظير المفصلي في الأذيات التنكسية للركبة - يوسف, علي (Latakia University Journal -Medical Sciences Series, 2017)
إن دور التنظير المفصلي في علاج التهاب المفصل التنكسي لا يزال موضع جدل.استعرضنا في دراستنا 22 حالة لالتهاب مفصل تنكسي عولجوا بالتنظير في مشفى الأسد الجامعي في اللاذقية لعام 2013 - 2015.كان الغرض من هذه الدراسة إظهار دور التنظير المفصلي في تحسين نوعية الحياة عند المريض وكان متوسط أعمار مرضانا 50 سنة (44-65) سنة، (12 رجل و10 نساء).شكا مرضانا من ألم ميكانيكي في معظم الحالات، وخضعوا لمسح شعاعي وسريري. تم استخدم مشعر Lequesne لتقييم الحالات قبل وبعد الجراحة.تمَّ إجراء غسيل للمفصل عند كل المرضى وإضافات حسب الحاجة استئصال غشاء زليلي موضع وتنضير واستئصال لأجزاء الغضروف الهلالي المتمزقة والغضروف المفصلي والمناقير.اقتصرت الاختلاطات بعد الجراحة على وفقط كسر أداة جراحية ضمن المفصل والتي تطلب الأمر نزعها بالتنظير. لم تسجل أي حالة إنتان أو التهاب وريد خثري أو ورم دموي.كانت النتائج مرضية بعد فترة متابعة 12 شهراً.تتعلق النتائج بالتخطيط الجيد قبل الجراحة وبالجراحة المجراة.إن التقدم التكنولوجي سمح بتوسيع مجال استطباب التنظير المفصلي.The role of arthroscopic debridement in the treatment of osteoarthritis of the knee is still controversy.We present in this work a retrospective series including 22 cases of gonarthrosis treated with arthroscopic debridement of the knee in the Traumatology orthopedic service in Alassad hospital in Lattakia in 2013 -2015.Our objective through this small series was to show the interest of arthroscopic debridement in this type of knee pathology, improving quality of life for patients.This study included 12 men (55%),and 10 women (45%) with an average age of 50 years ,with extremes ranging from 44 to 65 years. Clinically ,our patients complained of mechanical pain in the majority of cases .And all our patients were benefice a clinical examination and radiological .The Lequesene score was used to assess the condition of the knee before and after surgery.The surgical procedure consisted of a joint lavage ,and gestures at the demand : synovectomy, debridement and excision of fragments meniscal, cartilage or osteophyte.The postoperative complications were marked by a single case of intra-articular breaking instrument during surgery.No cases of hematoma or phlebitis or sepsis have been reported .The clinical results after a decline of 12 months were satisfactory.The results depend on good pre-operative planning, and irreproachable technical gesture.The experience of operators and technologic advances in has extended its indication.